활동성폐결핵환자에서 말초혈액단핵구의 Th1 및 Th2 cytokine 분비양상 - 박성학; Sung Hak Park; 이상학; Sang Hak Lee; 이숙영; Sook Young Lee; 문화식; Hwa Sik Moon; 현대성; Dae Sung Hyun; 신윤; Yoon Shin; et al. (The Korean journal of medicine, 1999)
T cell mediated immunity amlifies macrophage capacities to kill and digest the bacilli through production of interferon-γ (IFN-γ). The secreted cytokines of Th1 and Th2 cells can mutually regulate and inhibit each other's function. Therefore, the fine balance between the secreted cytokines is important for the resulting nature of tuberculosis. In this study, activation marker and cytokine production profiles were compared in patients with active tuberculosis and healthy control, and according to degree of radiographic extent and pleural involvement. Method：Forty-four patients with active pulmonary tuberculosis and 25 normal controls were recruited. We measuerd soluble interleukin-2 receptor(sIL-2R), IFN-r, IL-4 and IL-5 produced from blood mononuclear cells in vitro stimulation with phytohemagglutinin by ELISA. Results：The sIL-2R and IFN-γ from patients with active pulmonary tuberculosis were significantly lower than normal control, while IL-4 and IL-5 were not different between two group. The sIL-2R and IFN-r decreased in proportion to the extent of pulmonary involvement, and the sIL-2R and IFN-r from pulmonary tuberculosis with pleural effusion were significantly lower than those without pleural effusion. Conclusion：At the level of systemic T cells, development of tuberculosis is associated with diminished Th1 but not enhanced Th2 response.